Implicit facilitation effect on counterfactual and semifactual thinking - Macbeth, Guillermo Eduardo (2019)
The aim of this contribution is to provide novel evidence concerned with the mental representation of counterfactual and semifactual thinking. Previous studies found a facilitation effect for inferences derived from the representation of counterfactuals and semifactuals, but such facilitation was studied only for explicit propositions. The present contribution extends the evidence to implicit propositions. Two experiments were conducted, one focused on counterfactuals, the other on semifactuals. The first experiment suggests that counterfactuals promote the acceleration of the antecedent and the consequent, implicitly uttered. The second experiment found the same pattern for semifactuals, but only for the antecedent, also implicitly uttered. Taken together, this evidence supports the account proposed by the mental models´ theory of human thinking for counterfactuals and semifactuals. The results are discussed in the context of the psychology of reasoning.